Comportamento das precipitações mensais e anuais na Bacia do Rio Juruena - Castro, Joicy Marina de (2016)
The Seasonal variations of the components of the hydrological cycle allow tailor and deliver the urban, agricultural and environmental planning, determine the demand and availability of water resources, indicating critical periods, as well as providing subsidies that can reduce the impact caused by rainfall. This study aimed to analyze the spatial and temporal behavior of monthly and annual rainfall in the Juruena River Basin, the Amazon region of Mato Grosso. Data from 20 rain gauge stations were obtained from the Hidroweb system of National Water Agency for a period of 20 years. The monthly total failures were corrected by regional weighting, considering inserted stations in the Upper, Middle and Lower Juruena. It was observed the occurrence of two distinct seasons: rainy (october to april) and dry (may to september), irrespective of the watershed area. The annual totals ranged from 1158,2 to 2284,9 mm, with the highest rates observed in the Middle Juruena region. As for the monthly totals, the major and minor accumulations occur in january and july, with averages of 351,40 and 4,5 mm, respectively.